Optimalisasi Penerapan Sertifikasi Halal melalui Self Declare dalam Perspektif Kesadaran dan Kepatuhan Hukum : Studi Kasus pada Pelaku Usaha Mikro di Kabupaten Bangkalan - Abd. Mughni Jamil; Dery Ariswanto (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Halal certification through the self-declaration scheme is a system designed with the aim of making it easier for micro and small businesses to receive halal certificates for the products they design. Not only makes it easier to receive halal certification but also conveys good benefits for the benefit of humanity, especially for Muslims. This system is designed to increase the number of halal-certified MSE products, thereby increasing consumer confidence and opening up opportunities for sales of halal products and competitiveness. The advantage of the halal certification application process using the self-declaration method means that the issuance of certificates is faster than using submissions through the regular mechanism. The halal certification method through self-declaration comes into effect from 2021. The original purpose of this research is to increase knowledge, enlightenment and regulatory compliance in micro-business actors in order to achieve optimization of halal certification in Bangkalan Regency. This study uses a qualitative narrative research method using a phenomenological approach in this study, the reality that exists can be understood as something that arises in the enlightenment of researchers through certain approaches and explanations, which mention how the process becomes visible and real. This study shows that there is a lack of awareness of the importance of halal certification, micro and small business actors still lack information and understanding of the halal professional allowance, so that the application of the halal professional allowance is not optimal. the original results of this study are needed to convey an illustration of how the Regional Government needs to take part in overseeing the implementation of the BPJPH Law and provide protection to business actors.